Catalytic activity and effect of modifiers on Ni-based catalysts for the dry reforming of methane - Barroso Quiroga, Maria Martha (2010)
Ni catalysts supported on different ceramic oxides (Al2O3, CeO2, La2O3, ZrO2) were prepared by wet impregnation. The catalytic behavior toward hydrogen production through the dry reforming of methane using a fixed-bed reactor was evaluated under certain experimental conditions, and the catalyst supported on ZrO2 showed the highest stable activity during the period of time studied. The catalyst supported on CeO2 has a relatively good activity, but shows signs of deactivation after a certain time during the reaction. This catalyst was chosen to be studied after the addition of 0.5 wt% Li and K as activity modifiers. The introduction of the alkaline metals produces a reduction of the catalytic activity but a better stability over the reactant conversion time. The reverse water-gas shift reaction influences the global system of reactions, and as the results indicate, should be considered near equilibrium.